The effects of 4 different recovery strategies on repeat sprint-cycling performance - Argus, C. K.; Driller, M. W.; Ebert, T. R.; Martin, D. T.; Halson, S. L. (International Journal of Sports Physiology and Performance, 2013)
Purpose: To evaluate the effectiveness of different recovery strategies on repeat cycling performance where a short duration between exercise bouts is required. Methods: Eleven highly trained cyclists (mean ± SD; age = 31 ± 6 y, mass = 74.6 ± 10.6 kg, height = 180.5 ± 8.1 cm) completed 4 trials each consisting of three 30-s maximal sprints (S1, S2, S3) on a cycle ergometer, separated by 20-min recovery periods. In a counterbalanced, crossover design, each trial involved subjects performing 1 of 4 recovery strategies: compression garments (COMP), electronic muscle stimulation (EMS), humidification therapy (HUM), and a passive control (CON). The sprint tests implemented a 60-s preload (at an intensity of 4.5 W/kg) before a 30-s maximal sprint. Mean power outputs (W) for the 3 sprints, in combination with perceived recovery and blood lactate concentration, were used to examine the effect of each recovery strategy. Results: In CON, S2 and S3 were (mean ± SD) -2.1% ± 3.9% and -3.1% ± 4.2% lower than S1, respectively. Compared with CON, COMP resulted in a higher mean power output from S1 to S2 (mean ± 90%CL: 0.8% ± 1.2%; possibly beneficial) and from S1 to S3 (1.2% ± 1.9%; possibly beneficial), while HUM showed a higher mean power output from S1 to S3 (2.2% ± 2.5%; likely beneficial) relative to CON. Conclusion: The authors suggest that both COMP and HUM may be effective strategies to enhance recovery between repeated sprint-cycling bouts separated by ~30 min.